TINJAUAN KRIMINOLOGI TINDAK PIDANA NARKOTIKA YANG DILAKUKAN OLEH ANAK DI WILAYAH HUKUM POLRES 50 KOTA - Besse Patmawanti; Kiki Yulianda (UNES Law Review, 2020)
This study examines the Criminology Review of Narcotics Offenses committed by Children in the Legal Area of ​​the 50 City Police. This research is descriptive research. The approach method used in this research is a normative juridical approach as the main approach supported by an empirical juridical approach, using secondary and primary data collected through literature and field studies with data collection techniques through interviews and documentation. The results showed that: 1) by the children in the Legal Area of ​​the 50 City Police, first the factor of lack of parental attention, and feeling isolated so that they fall into narcotics. The second is the environmental factor in which to live and hang out in the community. The third is the factor of curiosity and trial and error that causes this crime of narcotics abuse to occur. Fourth is the factor of education which causes a lack of understanding of the dangers of drugs. 2) The efforts made by the 50 City Police to tackle the Narcotics Crime committed by children, which are divided into 2 efforts, namely Preventive Efforts, which are efforts made by the 50 City Police and carried out before the narcotics crime occurs in the form of campaigns, counseling, socialization. , family approaches, and dissemination of knowledge about the dangers of drugs. Meanwhile, the Repressive Effort is to take action in the form of investigations within the scope of schools and colleges in order to monitor drug trafficking among adolescents.